AB0279 Rapid3 is not longitudinally associated with das28-esr in patients with rheumatoid arthritis. (12th June 2018) - Boone, N.; Sepriano, A.; Janknegt, R.; van der Kuy, H.; Peeters, R.; Landewé, R.
Abstract : Background: The Routine Assessment of Patient Index Data 3 (RAPID3) is a patient reported outcome (PRO) proposed to conveniently measure disease activity in rheumatoid arthritis (RA) based on functioning, pain and global health scores. DAS28 (including PRO and objective measures) is the most frequently used score in clinical practice and research for that purpose [1] . It has been suggested that composite scores measuring PROs only (e.g. RAPID3) might add to the assessment of disease activity over time but this claim is yet to be formally tested. Objectives: In this study we evaluated a possible longitudinal association between RAPID3 and DAS28-ESR (including individual components) in patients with RA from daily clinical practice. Methods: Adult patients with RA on stable treatment with either conventional synthetic disease modifying drugs (csDMARDs) and/or biologic DMARDs (bDMARDs), followed in one centre, were included. Patients were followed every 3 months up to 3 years and in each visit both clinical and medication data was collected by rheumatologists/research nurses. The longitudinal association between RAPID3 (range: 0–30) with DAS28-ESR and its individual components [tender joint count (TJC; 0–28); swollen joint count (SJC; 0–28); patient global assessment (PGA; 0–10) and ESR (mm/h)] was tested (in separate models) by longitudinal generalised estimating equations (GEE) with auto-regression. Interactions between RAPID3 with gender (male vs female), VAS pain (≥5 vs<5), PGA (≥5 vs<5) and age (≥62 vs<62) at baseline were tested and if significant (p<0.20) and clinically relevant each model (either using DAS28 or its individual components as outcome) was stratified accordingly. Results: In total, 330 patients were included [mean (SD) age: 62 12 years, 68% female, baseline mean (SD) DAS28: 3.3 (1.4) and RAPID3: 11.5 (6)]. The mean (SD) follow-up period was 10.7 (9.7) months. Although, statistically significant, we only found a poor association between RAPID3 and DAS28-ESR over time (table 1). An increase of one unit in RAPID3 (0–30) was associated with an increase of only 0.1 units of DAS28-ESR. Gender, age, PGA and VAS pain were not found to meaningfully modify the association between RAPID3 and DAS28. A far stronger association was found between RAPID3 and the 'subjective components' [TJC: β=0.30 (95%: 0.20; 0.39); and PGA: β=0.31 (95%: 0.28; 0.35)] of DAS28-ESR, as compared to the 'objective components' (i.e., SJC and ESR; the latter only significant in males) (table 1). Conclusions: There is no meaningful longitudinal association between RAPID3 and DAS28. DAS28 captures objective signs of disease activity over time in RA while RAPID3 only captures subjective symptoms of RA. Reference: [1] Van der Heijde DM, et al. Development of a disease activity score based on judgment in clinical practice by rheumatologists. J Rheumatol1993.20:579–581. Disclosure of Interest: None declared